Behavioural response to combined insecticide and temperature stress in natural populations of Drosophila melanogaster. (17th March 2016) - Fournier‐Level, A.; Neumann‐Mondlak, A.; Good, R. T.; Green, L. M.; Schmidt, J. M.; Robin, C.
Abstract: Insecticide resistance evolves extremely rapidly, providing an illuminating model for the study of adaptation. With climate change reshaping species distribution, pest and disease vector control needs rethinking to include the effects of environmental variation and insect stress physiology. Here, we assessed how both long‐term adaptation of populations to temperature and immediate temperature variation affect the genetic architecture of DDT insecticide response in Drosophila melanogaster . Mortality assays and behavioural assays based on continuous activity monitoring were used to assess the interaction between DDT and temperature on three field‐derived populations from climate extremes (Raleigh for warm temperate, Tasmania for cold oceanic and Queensland for hot tropical). The Raleigh population showed the highest mortality to DDT, whereas the Queensland population, epicentre for derived alleles of the resistance gene Cyp6g1, showed the lowest. Interaction between insecticide and temperature strongly affected mortality, particularly for the Tasmanian population. Activity profiles analysed using self‐organizing maps show that the insecticide promoted an early response, whereas elevated temperature promoted a later response. These distinctive early or later activity phases revealed similar responses to temperature and DDT dose alone but with more or less genetic variance depending on the population. This change in genetic variance among populations suggests that selection particularly depleted genetic variance for DDT response in the Queensland population. Finally, despite similar (co)variation between traits in benign conditions, the genetic responses across population differed under stressful conditions. This showed how stress‐responsive genetic variation only reveals itself in specific conditions and thereby escapes potential trade‐offs in benign environments.